Increasing Brain-Derived Neurotrophic Factor (BDNF) in medial prefrontal cortex selectively reduces excessive drinking in ethanol dependent mice. (15th September 2018) - Haun, Harold L.; Griffin, William C.; Lopez, Marcelo F.; Solomon, Matthew G.; Mulholland, Patrick J.; Woodward, John J.; McGinty, Jacqueline F.; Ron, Dorit; Becker, Howard C.
Abstract: The neurotrophin Brain-Derived Neurotrophic Factor (BDNF) has been implicated in a number of neuropsychiatric disorders, including alcohol use disorder. Studies have shown that BDNF activity in cortical regions, such as the medial prefrontal cortex (mPFC) mediates various ethanol-related behaviors. We previously reported a significant down-regulation in Bdnf mRNA in mPFC following chronic ethanol exposure compared to control mice. The present study was conducted to extend these findings by examining whether chronic ethanol treatment reduces BDNF protein expression in mPFC and whether reversing this deficit via direct injection of BDNF or viral-mediated overexpression of BDNF in mPFC alters voluntary ethanol consumption in dependent and nondependent mice. Repeated cycles of chronic intermittent ethanol (CIE) exposure was employed to model ethanol dependence, which produces robust escalation of ethanol intake. Results indicated that CIE treatment significantly increased ethanol intake and this was accompanied by a significant decrease in BDNF protein in mPFC that lasted at least 72 h after CIE exposure. In a separate study, once dependence-related increased drinking was established, bilateral infusion of BDNF (0, 0.25, 0.50 μg) into mPFC significantly decreased ethanol intake in a dose-related manner in dependent mice but did not affect moderate drinking in nondependent mice. In a third study, viral-mediated overexpression of BDNF in mPFC prevented escalation of drinking in dependent mice but did not alter intake in nondependent mice. Collectively, these results provide evidence that adaptations in cortical (mPFC) BDNF activity resulting from chronic ethanol exposure play a role in mediating excessive ethanol drinking associated with dependence. Highlights: Ethanol dependence-related escalated drinking is accompanied by reduced BDNF protein expression in mPFC. Microinjection of BDNF into mPFC reversed ethanol dependence-related escalated drinking. Viral-mediated BDNF overexpression in mPFC prevented ethanol dependence-related escalated drinking. BDNF activity in mPFC may be a therapeutic target for reducing excessive drinking associated with ethanol dependence.